More Catholic than Rome; more reformed than Geneva: Joseph P. Cassidy and possibilities for renewal in the Church of England. Issue 1 (2nd January 2019) - Loades, Ann
ABSTRACT: This article traces the integration of theology, spirituality and ethics in the work of Dr Joseph P. Cassidy from his life as a Jesuit, then as a priest of the Roman Catholic Church and then of the Church of England, as well as the new possibilities his work opened up for re-thinking decision-making both in ecclesial groups and in social and political life, not least re-thinking the importance of the laity.